Growing up in a recession - Giuliano, Paola; Spilimbergo, Antonio (Bonn, 2012)
"Does the historical macroeconomic environment affect preferences for redistribution? We find that individuals who experienced a recession when young believe that success in life depends more on luck than effort, support more government redistribution and tend to vote for left parties. The effect of recessions on beliefs is long-lasting. Our findings are supported using evidence from three different datasets. First, we identify the effect of recessions on beliefs exploiting time and regional variation in macroeconomic conditions using data from the 1972-2010 General Social Survey. Our specifications control for non-linear time-period, life-cycle and cohort-effects as well as a host of background variables. Second, we rely on data from the National Longitudinal Survey of the High School Class of 1972 (NLS72) to corroborate the age-period-cohort specification and look at heterogeneous effects of experiencing a recession during early adulthood. Finally, our findings are also confirmed with a sample of 37 countries whose citizens experienced macroeconomic disasters at different points in history, using data from the World Value Survey."